2001
DOI: 10.1046/j.0953-816x.2001.01518.x
|View full text |Cite
|
Sign up to set email alerts
|

SB‐334867, a selective orexin‐1 receptor antagonist, enhances behavioural satiety and blocks the hyperphagic effect of orexin‐A in rats

Abstract: Intracerebroventricular (i.c.v.) administration of the novel hypothalamic neuropeptide orexin-A stimulates food intake in rats, and delays the onset of behavioural satiety (i.e. the natural transition from feeding to resting). Furthermore, preliminary findings with the selective orexin-1 receptor antagonist, SB-334867, suggest that orexin-A regulation of food intake is mediated via the orexin-1 receptor. At present, however, little is known about either the intrinsic effects of SB-334867 on the normal structur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
126
1
8

Year Published

2001
2001
2013
2013

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 214 publications
(142 citation statements)
references
References 42 publications
7
126
1
8
Order By: Relevance
“…Importantly, however, responding for food and nicotine rewards was similar under the PR schedule, in which SB-334867 selectively decreased nicotine intake without altering responding for food. Previously, it was shown that low doses of SB-334867 similar to those used in the present study did not alter arousal (20), sleep-wake cycles (20), food intake (21), or behavioral satiety (21) in rats. However, at higher doses (Ն10 mg/kg), SB-334867 decreased consumption of palatable high-fat food (22) and baseline food intake (21).…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, however, responding for food and nicotine rewards was similar under the PR schedule, in which SB-334867 selectively decreased nicotine intake without altering responding for food. Previously, it was shown that low doses of SB-334867 similar to those used in the present study did not alter arousal (20), sleep-wake cycles (20), food intake (21), or behavioral satiety (21) in rats. However, at higher doses (Ն10 mg/kg), SB-334867 decreased consumption of palatable high-fat food (22) and baseline food intake (21).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, hypocretin agonists and antagonists are also badly needed to assess the potential therapeutic value of this pathway for sleep and other disorders. Only one compound with moderate affinity and bioavailability, SB-334867, a Hcrtr1 antagonist, is available (Rodgers et al 2001). The phenotype of the system knockout, narcolepsy, indicate important and non redundant effects of this peptide system in the area of wake regulation, sleep consolidation and the cohesion of REM sleep.…”
Section: Other Perspectives In Hypocretin Researchmentioning
confidence: 99%
“…Although the exact mechanisms of MCH and orexin action are not yet known, treatment with either neuropeptide induces food intake in rodents, and their respective receptor antagonists ablate this response. 26,27 Leptin inhibits the expression of MCH and OX in leptin-deficient animals and blocks the fastinginduced activation of orexin neurons, although it does not affect the activation state of MCH neurons, suggesting that leptin regulates these two populations through separate mechanisms and/or through distinct populations of LepRb neurons. As OX regulates arousal as well as food intake (both of which are modulated by metabolic state fasting promotes the waking state, but food intake reduces alertness), 28 leptin may regulate OX neurons differently than it does MCH neurons to balance metabolic need and arousal.…”
Section: Leprb Loci That Regulate Hedonic Pathwaysmentioning
confidence: 99%